Vitamin B12 deficiency in the setting of nitrous oxide abuse: diagnostic challenges and treatment options in patients presenting with subacute neurological complications. Issue 6 (2nd November 2022) - Sluyts, Yasmine; Vanherpe, Pieternel; Amir, Rizvana; Vanhoenacker, Filip; Vermeersch, Pieter
ABSTRACT: Objective: It is well recognized that nitrous oxide abuse can lead to vitamin B12 deficiency presenting with neurological complications. Nevertheless, establishing this diagnosis can be challenging, and treatment guidelines are lacking. Methods: In this paper, we present a case series of eight patients and discuss the diagnostic challenges and treatment options for vitamin B12 deficiency due to nitrous oxide abuse presenting with neurologic complications. Results: Biochemical findings are not always straightforward and complementary testing is often necessary. Magnetic Resonance Imaging (MRI) revealed a longitudinally myelopathy extending over a long segment typically involving the dorsal columns of the cervical cord. To increase the lesion conspicuity, dedicated MRI sequences are needed. In our practice, we recommend the use of T2-weighted images (WI) with fat suppression (FS). Treatment consists of cessation of nitrous oxide abuse and supplementation with intramuscular injections of cobalamin. Due to a lack of treatment guidelines, we also describe the treatment schedule used in our neurology clinic and give a brief overview of treatment options suggested in the literature. Conclusion: We described diagnostic steps en treatment plans in patients presenting with subacute neurological complications due to nitrous oxide abuse. Abbreviations: crea: creatinine; HCy: homocysteine; MCA: 2-methylcitric acid; MMA: methylmalonic acid; MRI: magnetic resonance imaging; SEP: somatosensory evoked potentials